Respon Pertumbuhan Bibit Kelapa Sawit (Elaeis Guineensis Jacq) Akibat Pemberian Zat Pengatur Tumbuh Growtone Di Pre Nursery - Didik Anwar; Neng Susi; Vonny Indah Sari; Prastari, Cindytia (JURAGAN - Jurnal Agroteknologi, 2023)
This study aims to determine the effect and obtain the best dose of ZPT Growtone on the growth of oil palm seedlings (Elaesis guineensis Jacq) in pre-nursery. This research was carried out experimentally using a completely randomized design (CRD) with 5 treatments and 4 replications namely G0 (without treatment), G1 (ZPT Growtone 2 gr/l), G2 (ZPT Growtone 4 gr/l), G3 (ZPT Growtone 6 gr/l), G4 (ZPT Growtone 6 gr/l). The number of experimental units was 20 plots consisting of 16 plants and 4 plants as samples, the parameters observed were plant height, number of leaves, stem diameter and leaf area. The results of this study were that the administration of ZPT Growtone had a very significant effect on the growth of oil palm seedlings on the parameters of plant height, number of leaves, stem diameter and leaf area. The best growth of oil palm seedlings was found in the G3 treatment with a concentration of 6 g/l.